Seroprevalence of brucellosis among cows and sheep in Assiut province: A pilot study - Hamed, M; Kamaly, H; Abd Ellah, M; Mohammed, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Brucellosis is a common neglected zoonotic disease with a global geographic distribution that endangers human health and animal production. However, there is a scarcity of studies focusing on brucellosis in neglected regions such as Assiut governorate in Egypt. Therefore, the objective of this study was to investigate the prevalence of antibodies reactive to Brucella sp. in sheep and cows, as well as the associated risk factors, in Assiut governorate. A total of 184 sheep and 166 cows were included in the study, and their serum samples were subjected to screening using the Rose-Bengal plate test, followed by confirmation through the serum tube agglutination test. The overall seroprevalence of Brucella antibodies in sheep of 8.2% (15/184), while in cows, the seroprevalence was 1.2% (2/166). Among sheep, the seropositivity for Brucella abortus was 4.3% (8/184), whereas for Brucella melitensis, it was 6% (11/184). In cows, one cow displayed seropositivity for Brucella abortus, while the other exhibited mixed infection with both Brucella abortus and Brucella melitensis. Moreover, animals originating from villages bordering Sohag governorate demonstrated a higher risk of contracting brucellosis while other risk factors did not impact the occurrence of brucellosis. In conclusion, this study provides compelling evidence of the endemic nature of brucellosis in the investigated areas, with a particularly high prevalence observed in sheep. Both cows and sheep are susceptible to infection by either Brucella abortus or Brucella melitensis. To gain a comprehensive understanding of the epidemiological factors associated with infection, it is imperative to conduct large-scale surveys that incorporate molecular isolation of various Brucella species to facilitate the development of appropriate prevention strategies.